Trace element reference intervals in the blood of healthy green sea turtles to evaluate exposure of coastal populations. (January 2017) - Villa, C.A.; Flint, M.; Bell, I.; Hof, C.; Limpus, C.J.; Gaus, C.
Abstract: Exposure to essential and non-essential elements may be elevated for green sea turtles ( Chelonia mydas ) that forage close to shore. Biomonitoring of trace elements in turtle blood can identify temporal trends over repeated sampling events, but any interpretation of potential health risks due to an elevated exposure first requires a comparison against a baseline. This study aims to use clinical reference interval (RI) methods to produce exposure baseline limits for essential and non-essential elements (Na, Mg, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Mo, Cd, Sb, Ba, and Pb) using blood from healthy subadult turtles foraging in a remote and offshore part of the Great Barrier Reef. Subsequent blood biomonitoring of three additional coastal populations, which forage in areas dominated by agricultural, urban and military activities, showed clear habitat-specific differences in blood metal profiles relative to the those observed in the offshore population. Coastal turtles were most often found to have elevated concentrations of Co, Mo, Mn, Mg, Na, As, Sb, and Pb relative to the corresponding RIs. In particular, blood from turtles from the agricultural site had Co concentrations ranging from 160 to 840 μg/L (4–25 times above RI), which are within the order expected to elicit acute effects in many vertebrates. Additional clinical blood biochemistry and haematology results indicate signs of a systemic disease and the prevalence of an active inflammatory response in a high proportion (44%) of turtles from the agricultural site. Elevated Co, Sb, and Mn in the blood of these turtles significantly correlated with elevated markers of acute inflammation (total white cell counts) and liver dysfunction (alkaline phosphatase and total bilirubin). The results of this study support the notion that elevated trace element exposures may be adversely affecting the health of nearshore green sea turtles. Graphical abstract: Highlights: Trace element exposure baselines of offshore green turtle blood are presented. Exposure baselines are calculated using clinical reference interval (RI) methods. Nearshore turtle blood often exceeds our baseline RIs for Co, Sb, Mo, As, and Pb. Clinical health of nearshore turtles indicates signs of systemic health stress. The RIs are generally in agreement with published data indicating global utility. Abstract : Blood reference intervals (20 elements) were calculated for healthy green turtles from a remote region and were applied to 3 coastal groups whose clinical health markers correlated with elevated blood metals.